FINANCIAL SYSTEM ON EDUCATION IN THE HOLY QUR’AN - Zulham Zulham; Fachruddin Azmi; Achyar Zein (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to investigate the roles of financial system on education in the Holy Qur’an. Research was done by interpreting verses of holy Qur’an in relation to financial guidance specifically in education. As findings, there are several verses explaining about financial system on education, they are al-An'am; verse 38, Yâsîn; verse 12, al-Hashr; verse 18, and al-Anfâl; verse 60. These four verses are explaining about the importance of planning in financial on education. Moreover, in Al-An'am verse 135 has explained about the significance position of organizing, actuating and controlling. Furthermore, in Yasin; verse 12 and Al-Anfal; verse 60 has also talked more about the flexibility in arranging the financial institution on Islamic education, whilst others verses have explained deeply about the openness on financial sources in Islamic education as well. As the conclusion, financial on education becomes an excessive factor in corroborating sustainability the providing of education.    Keywords:  Financial on Education, Verses, the Holy Qur’an